2023
DOI: 10.3390/ijms24021435
|View full text |Cite
|
Sign up to set email alerts
|

Marine Natural Products with Activities against Prostate Cancer: Recent Discoveries

Abstract: Prostate cancer is the most common cancer in men, with over 52,000 new cases diagnosed every year. Diagnostics and early treatment are potentially hindered by variations in screening protocols, still largely reliant on serum levels of acid phosphatase and prostate-specific antigen, with tumour diagnosis and grading relying on histopathological examination. Current treatment interventions vary in terms of efficacy, cost and severity of side effects, and relapse can be aggressive and resistant to the current sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Consequently, the development of new drugs from marine resources has become a focal point of scientific research. Currently, there are approximately 17 marine-derived drugs approved by the FDA for international marketing [ 15 ], primarily used in anti-tumor and anti-viral treatments [ 16 , 17 ]. However, research on the neuroprotective properties of marine natural products is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the development of new drugs from marine resources has become a focal point of scientific research. Currently, there are approximately 17 marine-derived drugs approved by the FDA for international marketing [ 15 ], primarily used in anti-tumor and anti-viral treatments [ 16 , 17 ]. However, research on the neuroprotective properties of marine natural products is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon for marine protein hydrolysates to contain anticancer peptides encrypted within their parent proteins [40]. Several marine-derived compounds have been reported to exhibit anticancer properties in PCa models [41,42]. While there is a potentially wide range of mechanisms through which their anticancer effects may be mediated, in pre-clinical studies, these peptides have been shown to sensitize cancer cells to anticancer agents [43,44].…”
Section: Introductionmentioning
confidence: 99%